2016
DOI: 10.1016/j.vaccine.2016.04.089
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin and neuraminidase containing virus-like particles produced in HEK-293 suspension culture: An effective influenza vaccine candidate

Abstract: Virus-like particles (VLPs) constitute a promising alternative as influenza vaccine. They are non-replicative particles that mimic the morphology of native viruses which make them more immunogenic than classical subunit vaccines. In this study, we propose HEK-293 cells in suspension culture in serum-free medium as an efficient platform to produce large quantities of VLPs. For this purpose, a stable cell line expressing the main influenza viral antigens hemagglutinin (HA) and neuraminidase (NA) (subtype H1N1) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Interestingly, Gag-eGFP VLPs do not achieve the expected organized structure as Gag VLPs probably due to the eGFP fusion that alters the native budding process [59]. These differences could not be detected by TEM due to the interference of negative staining with the samples [11,36,60]. To our knowledge, this is the first time were Gag-eGFP VLP intraparticle organization is observed.…”
Section: Ultrastructural Analysismentioning
confidence: 78%
“…Interestingly, Gag-eGFP VLPs do not achieve the expected organized structure as Gag VLPs probably due to the eGFP fusion that alters the native budding process [59]. These differences could not be detected by TEM due to the interference of negative staining with the samples [11,36,60]. To our knowledge, this is the first time were Gag-eGFP VLP intraparticle organization is observed.…”
Section: Ultrastructural Analysismentioning
confidence: 78%
“…Pseudotype-based influenza genes delivery represents an alternative to successfully express HA in mammalian cells providing an efficacious vaccine when tested in chickens and mice ( 61 , 62 ). More recently, Venereo-Sanchez et al showed that HIV-Gag-based VLP displaying H1N1 induced a sustained immune response which provided full protection after lethal challenge with the homologous virus strain in mice ( 63 ). Of note, IDLVs used in our report were pseudotyped with VSV.G glycoprotein which may also contribute to the strength of the IDLV-induced immune responses by increasing the tropism of the vector.…”
Section: Discussionmentioning
confidence: 99%
“…For new strains, a recombinant protein can be used to generate the standard curve even though the binding affinity might vary depending on the nature of the sample (S4 Fig). Alternatively, a calibrating antigen can be produced and quantified using a method based on SDS-page as recently described [28]. HA concentrations obtained by dot blot were compared to values obtained in the hemagglutination assay and the SRID assay.…”
Section: Discussionmentioning
confidence: 99%